STRATEGI KOMUNIKASI PEMASARAN DIGITAL BERBASIS USER-GENERATED CONTENT (UGC) PADA SOSIAL MEDIA DAN PENGARUHNYA TERHADAP CONSUMER TRUST - Yeti Diah Wiyanti (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
The digital transformation has shifted transactional behavior toward online platforms, yet this evolution is overshadowed by rampant fraud risks and consumer fatigue toward formal advertisements (promo fatigue). To overcome these challenges, companies have begun integrating User-Generated Content (UGC) as a dynamic, two-way dialogic instrument. This study aims to analyze the core characteristics of UGC in digital marketing communication and examine the extent of its influence on building consumer trust. This study employs a descriptive qualitative approach utilizing the library research method. Secondary data were gathered through a systematic review of reputable scientific journals, textbooks, and industry reports published within the last 10 years. Data analysis followed the Miles and Huberman qualitative model, which comprises data condensation, data display, and conclusion drawing. The findings indicate that UGC is characterized by high authenticity, information transparency, and a non-commercial nature and functions as a powerful electronic Word of Mouth (e-WOM) agent. Theoretical analysis based on Social Proof Theory, Source Credibility Theory, and Consumer-Based Trust Theory demonstrates that UGC is a significant driver of consumer trust. Original content from real consumers minimizes information asymmetry and effectively satisfies the three core dimensions of trust: brand reliability, integrity, and competence. Nonetheless, this paper reveals an